KOMUNIKASI NON VERBAL KANURI BLANG PADA MASYARAKAT TANI UNTUK MENCIPTAKAN TANAM SERENTAK DI DESA KREUNG TINGGAI KECAMATAN SAMATIGA KABUPATEN ACEH BARAT - Khori Suci Maifianti (Universitas Teuku Umar, 2017)
Communication is done not only by words but also by non verbal activity that has been dealt. The farmers of Kreueng Tinggai, Samatiga, Aceh Barat have been done non verbal communication after ritual “kanuri blang”. This study used qualitative method, where the source of data were taken from observation, deep interview, and focus group dissussion (FGD). Non verbal communication used is flag. When the white flag waves is means that it is sowing time, and when the green flag waves, it is planting time. The colour of flag is used to acuelerate the information so the people are able to plant together. Keywords : Communication Non Verbal, Kanuri Blang, Community Farmers